New natural compound inhibitors of PDGFRA (platelet-derived growth factor receptor α) based on computational study for high−grade glioma therapy - Yang, Wenzhuo; Wang, Shengnan; Zhang, Xiangmao; Sun, Hu; Zhang, Menghan; Chen, Hongyu; Cui, Junxiang; Li, Jinyang; Peng, Fei; Zhu, Mingqin; Yu, Bingcheng; Li, Yifan; et al. (Frontiers in Neuroscience, 2023)
High-grade glioma (HGG) is a malignant brain tumor that is common and aggressive in children and adults. In the current medical paradigm, surgery and radiotherapy are the standard treatments for HGG patients. Despite this, the overall prognosis is still very bleak. Studies have shown that PDGFRA (platelet-derived growth factor receptor α) is an essential target to treat tumors and inhibiting the activity of PDGFRA can improve the prognosis of high-grade glioma. Thus, PDGFRA inhibitors are critical to developing drugs and cancer treatment. In our study, we selected Imatinib as the reference drug. A series of computer-aided technologies, such as Discovery Studio 2019 and Schrodinger, were used to screen and assess potential inhibitors of PDGFRA. The first step was to calculate the Libdock scores, then to analyze the pharmacological and toxicological properties. Following this, we docked the small molecules selected in the previous steps with PDGFRA to study their docking mechanism and affinity. In addition, molecular dynamics simulation was used to determine whether the ligand-PDGFRA complex was stable in nature. Based on our results, ZINC000008829785 and ZINC000013377891 might provide a solid foundation for drugs that inhibit PDGFRA in HGG. In addition to being safe drug candidates, these compounds had important implications for improving drugs targeting PDGFRA.